Discrete Element Simulation of Durability for Bionic Wheels of Mars Rover. (April 2020) - Lin, Y C; Yan, Y P; Yuan, B F; Liu, Y F; Zou, M
Abstract: Four kinds of bionic surfaces (convex, scale-like, ribbed and concave shape) for Mars rover wheels were designed to improve wheel durability. A discrete element wheel-soil simulation system was developed, and three-dimensional discrete element analysis and soil bin tests were conducted. The results show that the masses of the convex and scale-like forms increased by 5.4% and 17%, respectively, and that the tangential cumulative forces decreased by about 40% and 70%, respectively. The wear mass decreased by 53% and 47%, respectively, compared with a prototypical wheel. The simulation shows that the durability increased significantly. The average tangential cumulative forces of the concave and ribbed shapes increased by more than 50%, and the wear mass decreased by 35% and 32%, respectively, compared with a prototypical wheel. The simulation shows that the results were not definitive. The analysis shows that the durability of the wheels can be improved via bionic optimization method. These results therefore provide a basis and reference for the design and optimization of the Mars rover's wheel surface.